A Numerical Study on the Impact Resistant Capacity of RC Beams with Corroded Reinforcement. (2017) - Lu, Chi; Tamai, Hiroki; Sonoda, Yoshimi
Abstract: To evaluate the remaining service life and determine the appropriate timing and method for repair and reinforcement for the reinforced concrete (RC) structures, it is important to quantitatively evaluate the residual load capacity of RC structures deteriorated by rebar corrosion due to chloride attack or neutralization. There have been many studies on the load capacity during static loadings. However, for disaster-prone areas, the evaluation of the residual load should be conducted also against the dynamic and impact loads. In this study, to clarify the impact resistance of the RC beam members with rebar corrosion, a falling weight impact experiment is conducted on the RC beam specimen with accelerated deterioration. Based on the experimental results, the relationship between the degree of deterioration and impact resistance is clarified. To numerically simulate the rebar corrosion by FEM, FE modelling of RC beam with corroded rebar is proposed focusing on the following 3 factors related to the mass loss ratio of the rebar: the reduction of the cross-sectional area of the reinforcement is reproduced by adjusting the parameters of the rebar material; an interface element is defined to describe the reduction of the bond strength; the cracks are generated by subjecting expansion pressure to the concrete. Uneven corrosion model is introduced to simulate the actual corrosion result. By comparing the analytical result with the experimental result, it can be found that the experimental result is accurately reproduced.